Cellulose nanofibers from waste paper and their utilization as reinforcement materials in poly((R)-3-hydroxybutyrate-co-(R)- 3-hydroxyhexanoate bionanocomposite - Tengku Yasim Anuar, Tengku Arisyah; Sharip, Nur Sharmila; Megashah, Liana Noor; Ariffin, Hidayah; Muhamad Nor, Nor Azlin (Universiti Putra Malaysia Press, 2020)
Waste paper is the second-highest municipal solid waste collected in Malaysia and as current practice, it is recycled for further use in the manufacturing of low-grade products. Instead of continuously utilizing waste paper for low-grade products manufacturing, it can be used as a feedstock to produce high bioproducts such as cellulose nanofiber (CNF). Hence, this study explored the potential of waste paper as a feedstock for CNF production. The waste paper was subjected to a different number of cycles of wet disk milling (WDM): 0, 5, 10, 15 and 20 cycles. The presence of nano-sized cellulose was confirmed by FE-SEM micrographs, where CNF with diameter size 20 – 40 nm was formed after 10 cycles of milling. It was also revealed that the obtained CNF possessed appropriate properties as a reinforcement material. The tensile strength and Young’s modulus of poly((R)-3-hydroxybutyrate-co- (R)-3 hydroxyhexanoate (PHBHHx) increased by 19 and 12%, respectively after the reinforcement of 1% CNF. Overall, this study portrays that waste paper could be utilized as a raw material for CNF production, without the need for chemical pretreatment.